Price elasticity in import demand equations considering product quality: Estimates for the Brazilian economy (1996-2013) - Ariane Danielle Baraúna da Silva; Álvaro Barrantes Hidalgo (EconomiA, 2020)
Recent empirical studies argue that traditional trade models ignore product quality, usually leading to bias in price elasticities, which prevents the correct evaluation of trade determinants and the development of trade policies. This article quantifies the effect of quality on Brazilian imports. For that, we estimate import demand equations, including a proxy for the quality of imported goods, according to pooled data panel. Results show that price affects the demand for Brazilian imports more than quality, unlike literature results in developed countries. Introducing the quality proxy increased the price coefficient. This occurred more significantly in estimates for the manufacturing sector, supporting the hypothesis of elasticities bias when estimation does not consider product differentiation.
Keywords: F12; F14; 330; Elasticity of imports; Quality; Competitiveness; Differentiation